2019
DOI: 10.1039/c8ra09996k
|View full text |Cite
|
Sign up to set email alerts
|

Photoaddition reactions of N-benzylglycinates containing α-trimethylsilyl group with dimethyl acetylenedicarboxylate: competitive formation of pyrroles vs. β-enamino esters

Abstract: A study was conducted to gain insight into the preparative potential of photosensitized reactions of acyclic N-benzylglycinates containing an a-trimethylsilyl group with dimethyl acetylenedicarboxylate (DMAD). The photosensitizers employed in the reactions include 9,10-dicyanoanthracene (DCA), 1,4dicyanonaphthalene (DCN), rose bengal (RB) and fullerene C 60 . The results show that photoirradiation of oxygenated solutions containing the photosensitizers, glycinates and dimethyl acetylenedicarboxylate leads to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Further studies are underway to accumulate the information about the origin of chemoselectivity. Based on the analysis of photoadducts generated from above photosensitizer-promoted photoaddition reactions occurring between N--trimethylsilyl-N-alkyl glycinates and DMAD as well as the observation made from earlier studies, [21][22][23] feasible mechanistic pathways involved in both pyrroles and enamino-esters formation can be suggested, where in situ generated azomethine ylides and secondary amines are key intermediates. Specifically, as described in Scheme 6, a photochemical process is initiated by a SET process from glycinates 15 to excited state of photosensitizer ( S1 Sens and/or T1 Sens).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further studies are underway to accumulate the information about the origin of chemoselectivity. Based on the analysis of photoadducts generated from above photosensitizer-promoted photoaddition reactions occurring between N--trimethylsilyl-N-alkyl glycinates and DMAD as well as the observation made from earlier studies, [21][22][23] feasible mechanistic pathways involved in both pyrroles and enamino-esters formation can be suggested, where in situ generated azomethine ylides and secondary amines are key intermediates. Specifically, as described in Scheme 6, a photochemical process is initiated by a SET process from glycinates 15 to excited state of photosensitizer ( S1 Sens and/or T1 Sens).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, as described in Scheme 6, a photochemical process is initiated by a SET process from glycinates 15 to excited state of photosensitizer ( S1 Sens and/or T1 Sens). Taking into redox potentials of glycinates (i.e., oxidation potentials of glycinates, Eox) and photosensitizer (i.e., excited state reduction potentials of photosensitizers, * Ered), 21 the SET process from glycinates to photosensitizers (e.g., DCA, C60 and RB) should be thermodynamically favorable. 25 Since this favorable SET event takes place, as a result, aminium radicals of glycinates 16 and radical anions of photosensitizers (Sens •‾ ) are formed, in which Sens •‾ are subsequently interacted with molecular oxygen (O2), resulting in both ground state sensitizers and radical anions of oxygen (O2 •‾ ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the studies exploring application of amine SET photochemistry for the synthesis of nitrogen-containing compounds, interesting observation was made in our recent studies aiming at exploring photochemical behaviors of both a-trimethylsilyl and a-alkoxycarbonyl group containing N-benzylamines (i.e., N-a-trimethylsilyl-N-benzylglycinates). 10 The results showed that photoirradiation of N-a-trimethylsilyl-Nbenzylglycinates in the presence of molecular oxygen (O 2 ) and photosensitizer (PS) could convert starting tertiary amines to non-silyl containing secondary amines via hydrolytic cleavage of in situ formed iminium ions. This investigation suggested that a-trimethylsilyl group substituted tertiary amines can participate in photochemical hydroamination reactions with alkynes to produce enamine derivatives predominantly.…”
Section: Introductionmentioning
confidence: 99%